Company Tax Reform in the European Union - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2003)
The European Commission recently proposed to move towards a consolidated tax base for European multinational companies, to be allocated across EU member states through a system of formula apportionment. This paper argues that while the Commissions four alternative blueprints for company tax reform may reduce existing problems of transfer pricing, they will also create new distortions as long as existing tax rate differentials are maintained. The paper also analyzes the changes in international tax spillovers which will occur as a result of a switch from the current system of separate accounting to formula apportionment. The final part of the paper discusses whether more conventional corporate tax harmonization should still be a long term policy goal for the EU and presents quantitative estimates of the effciency gains from harmonization.
Keywords: H2; H7; 330; corporate tax reform in the EU; formula apportionment; tax harmonization; Unternehmensbesteuerung; Steuerreform; EU-Staaten